2019
DOI: 10.1021/acs.iecr.9b03861
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Thermal Conductivities for Epoxy Composites via Incorporating Poly(vinyl benzal)-Coated h-BN Fillers and Solvent-Assisted Dispersion

Abstract: A solvent-assisted diffusion method is developed here to prepare thermally conductive epoxy composites (EP) after hexagonal boron nitride (h-BN) was modified via poly (vinyl benzal) (PVB) noncovalent bond coating. The h-BN@ PVB with different PVB coating contents was prepared and verified by FT-IR, SEM, and TGA. Then, EPs loaded with 20 wt % filler were prepared by using these different PVB-coated particles to find the optimum value for PVB content. Finally, when introduced dimethyl sulfoxide solvent to the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Due to its chemical inertness and crystal structure, BN is often used together with functional molecules through noncovalent modification to improve the TC of polymer thermal composites. Yang et al [82] successfully prepared h-BN@PVB particles with different PVB coatings via the acetal reaction of polyvinyl alcohol (PVA) and benzaldehyde. ).…”
Section: Noncovalent Bond Modificationmentioning
confidence: 99%
“…Due to its chemical inertness and crystal structure, BN is often used together with functional molecules through noncovalent modification to improve the TC of polymer thermal composites. Yang et al [82] successfully prepared h-BN@PVB particles with different PVB coatings via the acetal reaction of polyvinyl alcohol (PVA) and benzaldehyde. ).…”
Section: Noncovalent Bond Modificationmentioning
confidence: 99%
“…A major use of BNNs is in polymeric nanocomposites for thermal transport properties and others that take advantage of the mechanical and chemically stable characteristics. The focus here is on the former, [7,13–25,33,95,102,112,133,135–138,142–266] and those who are interested in the latter are referred to other reviews …”
Section: Polymer/bnns Nanocompositesmentioning
confidence: 99%
“…The high oxidation resistance of BN is also critical to some of the applications, obviously unmatched by graphene nanosheets as well. As a result, there have been more recent investigations on the development of thermally conductive polymer/BNNs nanocomposites for thermal management and related uses [7,13–25,33,95,102,112,133,135–138,142–266] …”
Section: Polymer/bnns Nanocompositesmentioning
confidence: 99%
“…Surface modification has been demonstrated to be an effective way to improve the miscibility and dispersibility of BN and reduce the thermal resistance at the interface [15]. Yang et al utilized a poly(vinyl benzal) to modify BN via a noncovalent bond coating, which reached 0.89 W/(mꞏK) at 40 wt% h-BN@PVB loading using the solvent-assisted diffusion method and was 300% higher than the values of the neat epoxy resin [16]. Ma et al modified the BN by wet ball milling assisted with aqueous urea solution, and it was found that an 8 h milling time had the best enhancement of thermal conductivity, which was about 300% of that of pure epoxy resin [17].…”
Section: Introductionmentioning
confidence: 99%